Plurality of Inheritance Legal System for Indonesian Muslims: A Sociological Review - Muhammad Tsaqib Idary; Oyo Sunaryo Mukhlas; Beni Ahmad Saebani; Restu Khaliq (International Tatho Academics, 2024)
This qualitative study aims to identify the sociological construction of the implementation of legal principles in the inheritance system in Indonesia and its relevance to the Islamic inheritance system. The theory of receptio a contrario and the theory of structural functionalism as a legal sociology perspective are used to see how social construction is related to the implementation of the principle of justice, the principle of freedom of will, and the individual principle in the implementation of the inheritance system in a plural Indonesian society. This study finds the construction of social relations related to legal principles in the implementation of the national inheritance system with Islamic inheritance in Indonesia. The relational construction of these principles leads to the implementation of harmony between the implementation of the national inheritance legal system and the Islamic inheritance system so that both can run in an orderly and well-integrated manner. This study confirms that in sociological construction, the relationship between the principle of law enforcement and the social and cultural values of society cannot be dichotomized.